Masculinity and Femininity Symbols in South China Buddhist Temples: Psycho-Anthropological Perspective - Anas Ahmadi (Fakultas Bahasa dan Seni, 2023)
Studies on masculinity in the last ten years have increased along with men's awareness of themselves. The study of masculinity is in opposition to the study of femininity. In this regard, this research intersects both of them, namely the study of masculinity and femininity in the Quan Yin temple in China. This research explores the Quan Yin symbols in the Southern Chinese (Mahayana Buddhist) Temples. This study uses a psycho-anthropological perspective. This research with a qualitative approach uses data from the architecture of the Quan Yin Temple. Data collection techniques refer to ethnographic studies, namely (1) observation, (2) photography, (3) recording, and (4) interviewing. The results of the study show that the structure that appears in Quan Yin symbolism is a dyadic structure that is divided into oppositions of (i) temples with pagodas without pagodas, (ii) masculine-feminine, (iii) strong-gentle, (iv) closed (introversion)-open (extroversion), and (v) anima -animus. Meanwhile, in terms of the collective mediation function of symbolism, it is shown that Quan Yin has symbolism, which shows that Quan Yin is indeed the highest and surpasses gods or goddesses. Therefore, Quan Yin can manifest/become anything to help mankind on Earth. This research universally shows that masculinity and femininity are also present in religious symbols. Both masculinity and femininity are nondualities that cannot be separated. This concept is almost the same as yin and yang in Chinese human philosophy.